2014
DOI: 10.2131/jts.39.711
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of cyclooxygenase-2 (COX-2) by cannabidiolic acid in human breast cancer cells

Abstract: -Metastases are known to be responsible for approximately 90% of breast cancer-related deaths. Cyclooxygenase-2 (COX-2) is involved not only in inflammatory processes, but also in the metastasis of cancer cells; it is expressed in 40% of human invasive breast cancers. To comprehensively analyze the effects of cannabidiolic acid (CBDA), a selective COX-2 inhibitor found in the fiber-type cannabis plant (Takeda et al., 2008), on COX-2 expression and the genes involved in metastasis, we performed a DNA microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Cannabidiolic acid (CBDA), being a C3 -carboxyl derivative of CBD (2,4-dihydroxy-3-[(1R, 6R)-3-methyl-6-prop-1-en-2-ylcyclohex-2-en-1-[alpha]-6-pentylbenzoic acid), acts as a selective COX2 and prostaglandin endoperoxide synthase inhibitor and exhibits anti-inflammatory properties in human breast cancer cells [113]. It has been suggested that its action may be due to a weak affinity for CB1 and CB2 receptors ( Table 2) [114].…”
Section: Cb1/cb2 Receptorsmentioning
confidence: 99%
“…Cannabidiolic acid (CBDA), being a C3 -carboxyl derivative of CBD (2,4-dihydroxy-3-[(1R, 6R)-3-methyl-6-prop-1-en-2-ylcyclohex-2-en-1-[alpha]-6-pentylbenzoic acid), acts as a selective COX2 and prostaglandin endoperoxide synthase inhibitor and exhibits anti-inflammatory properties in human breast cancer cells [113]. It has been suggested that its action may be due to a weak affinity for CB1 and CB2 receptors ( Table 2) [114].…”
Section: Cb1/cb2 Receptorsmentioning
confidence: 99%
“…CBDA can interfere with COX-2 expression in MDA-MB-231 breast cancer cells, a highly aggressive triple-negative breast cancer cell line, and that CBDA exhibits selective inhibition of COX-2, as shown with purified COX-2 used as an enzyme source (Takeda et al, 2008(Takeda et al, , 2014a(Takeda et al, , 2017Takeda, 2013;Suzuki et al, 2017). The MDA-MB-231 cell line is also an accepted model of estrogen receptor α (ERα)-negative breast cancer as the cells do not require estrogens for growth, and MDA-MB-231 cells express all the subtypes of the peroxisome proliferator-activated receptors, PPARα, PPARβ/δ, and PPARγ (Suchanek et al, 2002a(Suchanek et al, , 2002bTakeda et al, 2013Takeda et al, , 2014bHirao-Suzuki et al, 2019b).…”
Section: Introductionmentioning
confidence: 95%
“…1A), a constituent of the fiber-type cannabis plant, is a biologically active component. For example, CBDA is reported to exert anti-bacterial effects (Appendino et al, 2008), cyclooxygenase-2 (COX-2) enzyme inhibition (Takeda et al, 2008;Takeda, 2013), down-regulation of COX-2 expression (Takeda et al, 2014a(Takeda et al, , 2017Suzuki et al, 2017), and anti-nausea/emetic effects (Bolognini et al, 2013;Rock and Parker, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, even the limited amount of information on this phytocannabinoid that has been published suggests that it may have a wide variety of actions and effects. Thus, it has been shown to inhibit breast cancer cell migration (Takeda et al, ) and to cause a down‐regulation of COX‐2 (Takeda et al, ).…”
Section: Introductionmentioning
confidence: 99%